Territorial identity and experiential tourism Ancash Case - Cruz Reyes, Fray Masias (2011)
The department of Ancash has 20 provinces, 166 districts and 345 rural communities which have history, traditions and culture, sheltered in its territory rich of tourist resources such as landscapes, gastronomy, patron festivities , music and dances that characterize and apart from the rest of the country and also within the region through valleys and altitudes. Tourist activity in the department is usually the sun on the beaches on the coast, recreation and culture in the Andean valleys in both the Callejón de Huaylas, as in the valley of the Marañón. Experimental tourism is now just beginning and it is practice only in some communities as Vicus, Olleros and Catac. It is shown with the return of people to their hometown accompanied with friends, motivated primarily by the festivities. This research has identified tourism resources by provinces and districts, transversed valleys in the Callejon de Huaylas, as the Rio Negro with spaces and attractive resources to the practice of experiential tourism. There has also been assessing and territorial identity by its inhabitants.